The legal protection of certified artisans with registration of Geographical Indication and the case of the certification of the handicraft of golden grass in the traditional communities of Jalapão (TO) - Pizzio, Alex (2020)
The advent of economic globalization has broadened the field of possibilities for actions aimed at regional development. In this sense, many regions have bet on the implementation of the Geographical Indication as an instrument capable of increasing economic dynamism, contributing to development in economic and social terms. The aim of this article is to evaluate whether the registration of Geographical Indication of handicraft products is an effective tool in the protection of these products and in the socio-community development. In the first part of the article, we make a brief review about the agency laws and protection mechanisms related to Industrial Property. In the second part, we carried out an analysis based on a concrete case: the certified golden grass handicrafts produced by the traditional communities of Jalapão, in Tocantins. The results of the study indicate that, even an instrument of valuation and protection of products and services disseminated on a global scale, such as SIG, offers only partial protection to golden grass crafts, since they cannot curb crimes such as the use of protected natural resources without proper authorization, appropriation of traditional knowledge and symbolic resources by third parties and the commercialization of pirated products in international markets.